Mental stress reduces performance and changes musculoskeletal loading in football-related movements - Auer, Simon; Kubowitsch, Simone; Süß, Franz; Renkawitz, Tobias; Krutsch, Werner; Dendorfer, Sebastian (Science and medicine in football, 2021)
Purpose: Football players have a high risk of leg muscle injuries, especially when exposed to mental stress. Hence, this study investigated the musculoskeletal response of elite youth football players during highly dynamic movements under stress. The hypothesis is that mental stress reduces performance and changes the muscular forces exerted. Materials & methods: Twelve elite youth football players were subjected to mental stress while performing sports-specific change-of-direction movements. A modified version of the d2 attention test was used as stressor. The kinetics are computed using inverse dynamics. Running times and exerted forces of injury-prone muscles were analysed. Results: The stressor runs were rated more mentally demanding by the players (p = 0.006, rs = 0.37) with unchanged physical demand (p = 0.777, rs = 0.45). This resulted in 10% longer running times under stress (p < 0.001, d = −1.62). The musculoskeletal analysis revealed higher peak muscle forces under mental stress for some players but not for others. Discussion: The study shows that motion capture combined with musculoskeletal computation is suitable to analyse the effects of stress on athletes in highly dynamic movements. For the first time in football medicine, our data quantifies an association between mental stress with reduced football players’ performance and changes in muscle force.